IPS in Supported Housing: Fidelity and Employment Outcomes Over a 4 Year Period - Roeg, Diana; de Winter, Lars; Bergmans, Cris; Couwenbergh, Chrisje; McPherson, Peter; Killaspy, Helen; van Weeghel, Jaap (Frontiers in Psychiatry, 2021)
Background People with severe mental illness have difficulties finding and maintaining competitive employment. This is particularly so for those living in supported housing who, by definition, have significant day-to-day support needs: in the Netherlands only 3 to 5% of people with serious mental health problems who live in supported housing are competitively employed. To support these people in finding and maintaining competitive employment, Individual Placement and Support (IPS) was introduced within supported housing services in the Netherlands in 2015. As this is the first country that broadly implemented IPS in supported housing settings, this paper will focus on the first results regarding feasibility and effects on employment in clients of IPS in this sector. Methods We investigated the feasibility and employment outcomes of delivering IPS in supported housing services using fidelity assessments and quarterly employment outcomes on IPS program level within eight supported housing organizations, and compared these with 21 mental health treatment organizations in the Netherlands over a four year period. We investigated possible reasons for our findings and their implications through qualitative evaluations of the IPS fidelity assessors’ notes and additional focus groups with IPS specialists and coordinators from supported housing services and fidelity assessors. Results The overall fidelity scores indicated reasonable implementation of the IPS model within both supported housing services and mental health services. However, there were differences between services with regard to specific fidelity items; mental health treatment organizations scored higher for team integration, whereas supported housing services scored higher for rapid job search and caseload size, diversity of jobs and employers. Our qualitative data suggested that the difference in team integration between the two sectors was due to differences in their organizational and financial structures, as well as in the specific needs of their clients. Conversely, supported housing services had better connections with employers which facilitated more rapid job searching and greater diversity in employment opportunities. The average total client employment rate did not significantly differ; and was 25.8% per quarter in supported housing services and 29.6% in mental health treatment services. Conclusion Implementing IPS in supported housing settings is both feasible and effective.